Development of sensory-motor synapses in the spinal cord of the frog. - Frank, E (1983)
The development and specificity of monosynaptic sensory-motor synapses were studied in the brachial spinal cord of bullfrog tadpoles. Intracellular and extracellular recordings were made from motoneurones innervating several different muscles of the forelimb. Excitatory synaptic potentials (e.p.s.p.s) were elicited by stimulation of various peripheral muscle nerves. Sensory and motor axons in the triceps brachii muscle nerves were electrically excitable at stage XIII, the earliest stage studied. Their conduction velocities were 0.2-0.4 m/s. These velocities increased during subsequent development so that by stage XXII they were approximately 5 m/s. Before stage XVII, synaptic potentials evoked in motoneurones by stimulation of the triceps sensory fibres had a long central latency and fatigued easily. These potentials were probably mediated polysynaptically. At stage XVII, the first short-latency triceps synaptic potentials appeared. They had central latencies of less than 3 ms and represented the direct, monosynaptic input from muscle sensory cells on to motoneurones. During subsequent development the percentage of triceps motoneurones innervated by triceps sensory fibres increased, while the number of long-latency polysynaptic inputs decreased. Both the electrical and chemical components, characteristic of these monosynaptic e.p.s.p.s in adult frogs, were prominent from the time the e.p.s.p.s first appeared. The pattern of innervation of brachial motoneurones by triceps sensory afferents was specific from the beginning. Triceps sensory fibres innervated most triceps motoneurones but very few subscapular or pectoralis motoneurones, just as in adult frogs. At no time were there appreciable numbers of 'aberrant' connexions. The developmental time course of several different classes of sensory-motor connexions was similar. Thus the synaptic specificity of this system cannot be explained by a differential timing of synaptogenesis.